Designer based Fourier transformed voltammetry: A multi-frequency, variable amplitude, sinusoidal waveform - Tan, Y; Stevenson, G; Baker, R; Elton, D; Gillow, K; Zhang, J; Bond, A; Gavaghan, D (2009)
Fourier transform methods allow custom-designed complex waveforms to be used in ac voltammetry. Commonly a single wave or sum of sine waves of variable angular frequency (ω) but constant amplitude (Δ E) superimposed onto a dc ramp are employed. In the present case, a custom-designed waveform consisting of a combination of eight sine waves is introduced, with the property that each sine wave within the composite waveform has the property Δ Ei ∝ 1 / sqrt(ωi) where i represents the i th sine wave. Frequencies (and amplitudes) employed in a single experiment cover the range from 34.94 Hz (20 mV) to 1970.01 Hz (2.66 mV). Reversibility is readily detected via use of this designer waveform by noting a constant peak height (Ip (ω t)) for all eight frequencies, whereas Ip (ω t) values decrease in a characteristic manner with increasing frequency for a quasi-reversible process or when uncompensated resistance is present, as demonstrated experimentally and theoretically. Importantly, background charging current contributions do not increase to a level that makes measurement of faradaic current difficult at high frequencies and hence charging current is readily corrected for over the entire frequency range of interest. © 2009 Elsevier B.V. All rights reserved.